Hepatosellüler karsinomada glut1 inhibitörü bay-876’nın hepg2 hücrelerinde ve steatoz hücre modelinde glukoz alımı ve hücre çoğalmasına etkisi - AYDIN OMAY, BANU; CABADAK, HÜLYA (My University, 2022)
Hepatocellular carcinoma is one of the deadly cancers with a significant incidence worldwide. In cancer cells, aerobic glycolysis increases with the Warburg effect. Glucose transport across the cell membrane becomes important at this stage. It has been found that there is an increase in GLUT1 expression in various cancers. BAY-876 is a new generation GLUT1 inhibitor. The affinity of BAY-876 for GLUT1 was found to be approximately 100 times higher than for other glucose transporters. HepG2 cells will be used in molecular analyzes to investigate the role of this novel GLUT1 inhibitor in GLUT1-mediated cell proliferation and glucose uptake into the cell.The effect of BAY-876 on glucose uptake was investigated in the case of bioenergetic stress by applying metformin, an insulin-sensitizing agent with strong antihyperglycemic properties, and in hypoxic environment by applying CoCl2 treatment. A steatosis cell model was created using oleic acid and palmitic acid. We aimed to investigate the effects of BAY-876 on cell proliferation and glucose uptake in HepG2 cell line and HepG2 steatosis cell model. Drugs were added to the culture medium. its effect on cell proliferation was investigated with the BrDU method. Cell proliferation, glucose uptake and colony formation were investigated in HepG2 cell line and HepG2 steatosis cell model in the presence and absence of BAY-876. BAY-876 inhibits cell proliferation and reduces glucose uptake in HepG2 cells and steatosis cell model. BAY-876 was also found to reduce glucose uptake in normal and steatosis cell models under bioenergetic and hypoxic stress conditions. It is predicted that our study will contribute to the literature, provide a different perspective to anticancer drug research studies of GLUT1 inhibitor and contribute to the elucidation of the signal transmission mechanism of hepatocellular carcinoma.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyofizik; Medicine; Health Sciences; Fundamental Medical Sciences; Biophysics; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; TIP, GENEL & DAHİLİ; BİYOFİZİK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MEDICINE, GENERAL & INTERNAL; BIOPHYSICS; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Life Sciences; Hepatocellular carcinoma; BAY-876; steatosis; metformin